Light and temperature as triggers for surface filamentous green algal blooms in shallow freshwater systems - Hannah R. Kemp; Alexandra Zieritz; Stephen J. Dugdale; Nico R. Helmsing; Suzanne Wiezer; Lisette N. de Senerpont Domis; Stephen C. Maberly; Martyn Kelly; Suzanne McGowan (Limnology and Oceanography, 2025)
Blooms of filamentous green algae (FGA) form dense mats at the surface of shallow freshwaters and have multiple negative impacts on aquatic ecosystem functions, services, and aesthetics. Although nutrient enrichment in freshwaters is a primary driver of excessive FGA growth, much less is known about other abiotic factors controlling bloom growth rate, extent, and timing. We performed a series of indoor mesocosm (Limnotron) experiments to investigate the effects of photosynthetically active radiation irradiance, photoperiod, and water temperature on the growth and surface bloom formation of FGA using underwater and surface photography. The results revealed that a minimum daily light integral of ~ 13.2 mol m −2 d −1 (a combination of photosynthetically active radiation irradiance measured at the water surface and daylength) was required for bloom formation and substantial FGA growth. Surface blooms did not occur at short daylengths (i.e., 8 h), whereas a long daylength (i.e., 16 h) allowed more time for photosynthetically derived gas bubbles to accrue in the FGA masses, making them rise to the water surface through buoyancy. We also found that temperatures between 16°C and 22°C were optimal for FGA to form surface blooms. As freshwater ecosystems are increasingly impacted by climate change, our study sheds new light on factors affecting the occurrence of surface blooms and helps identify when waterbodies may be at risk of FGA blooms in the future.

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

Non-native freshwater molluscs: a brief global review of species, pathways, impacts and management strategies - Manuel Lopes-Lima; André Lopes-Lima; Lyubov Burlakova; Karel Douda; Álvaro Alonso; Alexander Karatayev; Ting Hui Ng; Maxim Vinarski; Alexandra Zieritz; Ronaldo Sousa (Hydrobiologia, 2025)

Review of the globally invasive freshwater mussels in the genus Sinanodonta Modell, 1945 - Karel Douda; Alexandra Zieritz; Barbora Vodáková; Maria Urbańska; Ivan N. Bolotov; Jana Marková; Elsa Froufe; Arthur E. Bogan; Manuel Lopes-Lima (Hydrobiologia, 2025)
In this review, we synthesize the current knowledge of the biology, ecology, and impact of Sinanodonta freshwater mussels (Bivalvia, Unionidae), native to East Asia, that have successfully invaded Europe, Central America, North Africa, and several Asian regions. The main introduction pathways of Sinanodonta were reconstructed based on DNA sequence data and distribution records. We show that invasive lineages of Sinanodonta belong to three species, namely, S. woodiana s. str. (“temperate invasive” lineage), S. pacifica (“tropical invasive” lineage), and S. lauta . Their generalist fish-dispersed larvae, short life span, high fecundity, use by humans for multiple purposes, and ability to establish populations in anthropogenically disturbed conditions were identified as crucial traits driving their invasions. Information on the consequences is scarcer, but Sinanodonta can impact native species through larval parasitism, host fish/food competition, and parasite transmission. In addition, ecosystem effects through their filtration—biodeposition—excretion activity and the occurrence of massive die-offs were detected. Ecosystem services and disservices have not yet been quantified, even at local scales, and management methods in the invasive range are understudied. A better understanding of Sinanodonta ecology, impacts, and management options is urgently needed to make informed decisions and set realistic and impactful restoration goals.

Prioritising challenges and actions for freshwater conservation in a tropical biodiversity hotspot - Alexandra Zieritz; Christopher Gibbins; Yixiong Cai; Farah Diba; Lydia X. Gan; Manuel Lopes-Lima; Jose Christopher E. Mendoza; John Morse; Ting Hui Ng; Elysia X.P. Toh; John Pfeiffer; Bi Wei Low; et al. (Biological Conservation, 2024)

A roadmap for the conservation of freshwater mussels in Europe - Ronaldo Sousa; Tadeusz Zając; Dariusz Halabowski; Olga V. Aksenova; Yulia V. Bespalaya; Francisco Carvalho; Paulo Castro; Karel Douda; Janine P. da Silva; Noé Ferreira‐Rodríguez; Juergen Geist; Clemens Gumpinger; et al. (Conservation Biology, 2023)
Europe has a long history of human pressure on freshwater ecosystems. As pressure continues to grow and new threats emerge, there is an urgent need for conservation of freshwater biodiversity and its ecosystem services. However, whilst some taxonomic groups, mainly vertebrates, have received a disproportionate amount of attention and funds, other groups remain largely off the public and scientific radar. Freshwater mussels (Bivalvia, Unionida) are an alarming example of this conservation bias and here we point out six conceptual areas that need immediate and long‐term attention: knowledge, threats, socioeconomics, conservation, governance and education. The proposed roadmap aims to advance research, policy and education by identifying the most pressing priorities for the short‐ and long‐term conservation of freshwater mussels across Europe.

Freshwater mussel conservation: A global horizon scan of emerging threats and opportunities - David C. Aldridge; Isobel S. Ollard; Yulia V. Bespalaya; Ivan N. Bolotov; Karel Douda; Juergen Geist; Wendell R. Haag; Michael W. Klunzinger; Manuel Lopes‐Lima; Musa C. Mlambo; Nicoletta Riccardi; Ronaldo Sousa; et al. (Global Change Biology, 2023)
We identified 14 emerging and poorly understood threats and opportunities for addressing the global conservation of freshwater mussels over the next decade. A panel of 17 researchers and stakeholders from six continents submitted a total of 56 topics that were ranked and prioritized using a consensus‐building Delphi technique. Our 14 priority topics fell into five broad themes (autecology, population dynamics, global stressors, global diversity, and ecosystem services) and included understanding diets throughout mussel life history; identifying the drivers of population declines; defining metrics for quantifying mussel health; assessing the role of predators, parasites, and disease; informed guidance on the risks and opportunities for captive breeding and translocations; the loss of mussel–fish co‐evolutionary relationships; assessing the effects of increasing surface water changes; understanding the effects of sand and aggregate mining; understanding the effects of drug pollution and other emerging contaminants such as nanomaterials; appreciating the threats and opportunities arising from river restoration; conserving understudied hotspots by building local capacity through the principles of decolonization; identifying appropriate taxonomic units for conservation; improved quantification of the ecosystem services provided by mussels; and understanding how many mussels are enough to provide these services. Solutions for addressing the topics ranged from ecological studies to technological advances and socio‐political engagement. Prioritization of our topics can help to drive a proactive approach to the conservation of this declining group which provides a multitude of important ecosystem services.

High rates of biodeposition and N-excretion indicate strong functional effects of mussels (Bivalvia: Unionida) in certain anthropogenic tropical freshwater habitats - Alexandra Zieritz; Wei Ning Chan; Suzanne McGowan; Christopher Gibbins (Hydrobiologia, 2021)
The functional roles of freshwater mussels (Unionida) in tropical systems are poorly understood. We quantified the effects of mussel filtration, excretion and deposition in three anthropogenic tropical systems, i.e. a man-made lake, abandoned mining pool and rice paddy channel. Sinanodonta cf. woodiana (non-native) was present at all three sites, whilst Pilsbryoconcha compressa (native) was present in the channel only. Clearance rates, biodeposition rates and effects on suspended algal pigment and dissolved nutrient concentrations were quantified in controlled, replicated experiments in laboratory tanks with water from original habitats. Clearance rates were generally low and did not explain the high biodeposition rates observed. A considerable proportion of the natural diet of these populations may therefore consist of material that was not available in tanks, i.e. benthic or deposited algae. Deposition rates in lake and channel populations exceeded published rates from temperate and Mediterranean habitats, presumably due to prevalence of non-palatable material and/or higher metabolic rates in tropical systems. The presence of S. cf. woodiana but not P. compressa led to a strong increase in total ammonia nitrogen concentrations and N:P ratios, exceeding estimations from other systems. This study suggests that freshwater mussels play different functional roles in anthropogenic tropical habitats than in temperate systems.

The role of anthropogenic habitats in freshwater mussel conservation - Ronaldo Sousa; Dariusz Halabowski; Anna M. Labecka; Karel Douda; Olga Aksenova; Yulia Bespalaya; Ivan Bolotov; Juergen Geist; Hugh A. Jones; Ekaterina Konopleva; Michael W. Klunzinger; Carlos A. Lasso; et al. (Global Change Biology, 2021)
Anthropogenic freshwater habitats may provide undervalued prospects for long‐term conservation as part of species conservation planning. This fundamental, but overlooked, issue requires attention considering the pace that humans have been altering natural freshwater ecosystems and the accelerated levels of biodiversity decline in recent decades. We compiled 709 records of freshwater mussels (Bivalvia, Unionida) inhabiting a broad variety of anthropogenic habitat types (from small ponds to large reservoirs and canals) and reviewed their importance as refuges for this faunal group. Most records came from Europe and North America, with a clear dominance of canals and reservoirs. The dataset covered 228 species, including 34 threatened species on the IUCN Red List. We discuss the conservation importance and provide guidance on how these anthropogenic habitats could be managed to provide optimal conservation value to freshwater mussels. This review also shows that some of these habitats may function as ecological traps owing to conflicting management practices or because they act as a sink for some populations. Therefore, anthropogenic habitats should not be seen as a panacea to resolve conservation problems. More information is necessary to better understand the trade‐offs between human use and the conservation of freshwater mussels (and other biota) within anthropogenic habitats, given the low number of quantitative studies and the strong biogeographic knowledge bias that persists.

Towards the conservation of Borneo’s freshwater mussels: rediscovery of the endemic Ctenodesma borneensis and first record of the non-native Sinanodonta lauta - Alexandra Zieritz; Hussein Taha; Manuel Lopes-Lima; John Pfeiffer; Kong Wah Sing; Zohrah Sulaiman; Suzanne McGowan; Khairul Adha A.Rahim (Biodiversity and Conservation, 2020)
The freshwater mussel fauna of Borneo is highly endemic, with at least 11 species being unique to that island. Most of these species have not been recorded for at least 50 years owing to a lack of sampling effort and large-scale habitat destruction and degradation. Surveys conducted in 2016 across much of Malaysian Borneo failed to locate four out of five native species historically recorded in the study area. The present study aimed to determine the diversity and distribution of freshwater mussels of Brunei and adjacent Limbang Division, Malaysia. In 2018, we conducted interviews with locals, recorded environmental data and surveyed mussels at 43 sites, and conducted interviews at a further 38 sites. Only one population of native mussels, i.e. Ctenodesma borneensis , was found in a small tributary of the Limbang River situated in a patch of intact rainforest, representing the first record of this Bornean endemic genus since 1962. In addition, Sinanodonta lauta was found in a pond in Lawas district, representing the first record of this species outside its native East Asian distribution. Our data suggest that C. borneensis can sustain populations in relatively undisturbed habitats and is likely to have suffered population losses across northern Borneo. The first molecular phylogenetic analysis (COI + 28S) including an endemic Bornean freshwater mussel genus revealed that Ctenodesma is phylogenetically divergent from all other previously sampled lineages, rendering it a particularly valuable conservation target.

Effects of mussels on nutrient cycling and bioseston in two contrasting tropical freshwater habitats - Alexandra Zieritz; Farah Najwa Mahadzir; Wei Ning Chan; Suzanne McGowan (Hydrobiologia, 2019)

Revisiting the North American freshwater mussel genus Quadrula sensu lato (Bivalvia Unionidae): Phylogeny, taxonomy and species delineation - Manuel Lopes‐Lima; Lyubov Burlakova; Alexander Karatayev; André Gomes‐dos‐Santos; Alexandra Zieritz; Elsa Froufe; Arthur E. Bogan (Zoologica Scripta, 2019)
Freshwater mussels (Bivalvia, Unionidae) have suffered strong declines over the last century. High morphological plasticity of Unionidae causes disturbances in their systematics and taxonomy, hampering conservation efforts. Species that have historically been placed under the North American genus Quadrula have suffered from numerous taxonomic and species delineation problems since its inception. Four genera are presently recognized within Quadrula sensu lato, that is, Cyclonaias , Quadrula , Theliderma and Tritogonia , but their phylogenetic basis remains incompletely tested. In the present study, we reconstructed several two‐marker (mtDNA cytochrome c oxidase subunit I—COI and NADH dehydrogenase subunit 1—ND1) phylogenies with newly collected specimens and all previously available sequences covering most species within this group. We then delineated the species within the group using an integrative approach with the application of molecular statistical methods, morphometric (Fourier Shape) analyses and geographic distribution data. Four clades corresponding to these genera were consistently recovered in all phylogenies. To validate the generic status of these clades, molecular analyses were complemented with morphological, anatomical and ecological data compiled from the literature. Several revisions are here proposed to the current systematics and taxonomy of these genera, including the synonymization of Cyclonaias asperata under Cyclonaias kieneriana ; the inclusion of Quadrula apiculata and Quadrula rumphiana under Quadrula quadrula ; the placement of Quadrula nobilis under Tritogonia ; and finally the separation of the Mobile River basin populations of Theliderma metanevra as a new species, that is, Theliderma johnsoni n. sp. The conservation implications of the proposed changes are then discussed.

Diversity, biogeography and conservation of freshwater mussels (Bivalvia: Unionida) in East and Southeast Asia - Alexandra Zieritz; Arthur E. Bogan; Elsa Froufe; Olga Klishko; Takaki Kondo; Uthaiwan Kovitvadhi; Satit Kovitvadhi; Jin Hee Lee; Manuel Lopes-Lima; John M. Pfeiffer; Ronaldo Sousa; Tu Van Do; et al. (Hydrobiologia, 2018)

Lifting the curtain on the freshwater mussel diversity of the Italian Peninsula and Croatian Adriatic coast - Elsa Froufe; Manuel Lopes-Lima; Nicoletta Riccardi; Serena Zaccara; Isabella Vanetti; Jasna Lajtner; Amílcar Teixeira; Simone Varandas; Vincent Prié; Alexandra Zieritz; Ronaldo Sousa; Arthur E. Bogan (Biodiversity and Conservation, 2017)

Changes in pathways and vectors of biological invasions in Northwest Europe - Alexandra Zieritz; Belinda Gallardo; Simon J. Baker; J. Robert Britton; Johan L. C. H. van Valkenburg; Hugo Verreycken; David C. Aldridge (Biological Invasions, 2017)

Who lives where? Molecular and morphometric analyses clarify which Unio species (Unionida, Mollusca) inhabit the southwestern Palearctic - Elsa Froufe; Duarte V. Gonçalves; Amílcar Teixeira; Ronaldo Sousa; Simone Varandas; Mohamed Ghamizi; Alexandra Zieritz; Manuel Lopes-Lima (Organisms Diversity & Evolution, 2016)

Trans-national horizon scanning for invasive non-native species: a case study in western Europe - Belinda Gallardo; Alexandra Zieritz; Tim Adriaens; Céline Bellard; Pieter Boets; J. Robert Britton; Jonathan R. Newman; Johan L. C. H. van Valkenburg; David C. Aldridge (Biological Invasions, 2016)

Spatio-temporal distribution patterns of three stream-dwelling freshwater mussel species: towards a strategy for representative surveys - Alexandra Zieritz; Juergen Geist; Bernhard Gum (Hydrobiologia, 2014)

Shell ecophenotype in the blue mussel (Mytilus edulis) determines the spatial pattern in foraging behaviour of an oystercatcher (Haematopus ostralegus) population - Alexandra Zieritz; Gemma Clucas; Lauren Axtmann; David C. Aldridge (Marine Biology, 2012)